Porous Organic Cage-Based Quasi-Solid-State Electrolyte with Cavity-Induced Anion-Trapping Effect for Long-Life Lithium Metal Batteries - Qin, Wei‑Min; Li, Zhongliang; Su, Wen‑Xia; Hu, Jia‑Min; Zou, Hanqin; Wu, Zhixuan; Ruan, Zhiqin; Cai, Yue‑Peng; Li, Kang; Zheng, Qifeng (Nano-Micro Letters, 2024)
Porous organic cages (POCs) with permanent porosity and excellent host–guest property hold great potentials in regulating ion transport behavior, yet their feasibility as solid-state electrolytes has never been testified in a practical battery. Herein, we design and fabricate a quasi-solid-state electrolyte (QSSE) based on a POC to enable the stable operation of Li-metal batteries (LMBs). Benefiting from the ordered channels and cavity-induced anion-trapping effect of POC, the resulting POC-based QSSE exhibits a high Li+ transference number of 0.67 and a high ionic conductivity of 1.25 × 10−4 S cm−1 with a low activation energy of 0.17 eV. These allow for homogeneous Li deposition and highly reversible Li plating/stripping for over 2000 h. As a proof of concept, the LMB assembled with POC-based QSSE demonstrates extremely stable cycling performance with 85% capacity retention after 1000 cycles. Therefore, our work demonstrates the practical applicability of POC as SSEs for LMBs and could be extended to other energy-storage systems, such as Na and K batteries. Highlights: 1 A porous organic cage (POC)-based quasi-solid-state electrolyte (QSSE) with cavity-induced anion-trapping effect was rationally designed to enable the stable operation of Li-metal batteries. 2 The POC-based QSSE exhibits a high Li+ transference number of 0.67 and a high ionic conductivity of 1.25×10−4 S cm−1 with a low activation energy of 0.17 eV. 3 The POC-based QSSE demonstrates a highly reversible Li plating/stripping cycling for 2000 h and superior Li||LFePO4 cycling for thousands of cycles at room temperature.